Rendahnya persepsi masyarakat terhadap pemakaian gigitiruan di Desa Ujung Rambung, Kecamatan Pantai Cermin, Kabupaten Serdang Bedagai Minor perception of denture wear’s at Ujung Rambung Village, Pantai Cermin Subdistrict, Serdang Bedagai Regency - Dwi Tjahyaning Putranti; Helly Chandra (DiscoverSys Inc., 2011)
Individual perceptions towards denture wear’s are different from one to another, which are affected by number andlocation of missing teeth, age, sex, functional factors, esthetic, cultural factors, socioeconomy and education. Thepurpose of this study is to analyze the perceptions towards denture replacement among a rural community whoexperienced tooth loss based on age groups, sex and education in Desa Ujung Rambung Kecamatan Pantai CerminKabupaten Serdang Bedagai in February 2010. This study was an analytical observatory study. Samples are 200subjects who lost at least one tooth, excluding third molar. Chi-square test shows no significant difference betweenperceptions of appearance, mastication and speech and age groups, no significant difference between perceptions ofappearance, mastication and speech and sex, and no significant difference between perceptions of mastication andspeech and education (p>0,05), but shows statistically significant difference between perception of appearance andeducation (p=0,004). It can be concluded that the overall perceptions of the rural community is poor.